Competition and Incentives - Klaus Schmidt; Lisa Fey; Carmen Thoma (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
We report on two experiments that identify non-monetary incentive effects of competition. As the number of competitors increases, monetary incentives to engage in cost reduction tend to decrease. We test the hypothesis that there are non-monetary incentive effects of competition going in the opposite direction. In the experiments we change the number of competitors exogenously keeping the monetary incentives to spend effort constant. The first experiment shows that subjects spend significantly more effort in duopolistic and oligopolistic markets than in a monopoly. The second experiment focuses on social comparisons as one potential mechanism for this effect. It shows that competition turns the effort decisions of competing managers into strategic complements.
Keywords: D03; L10; O31; 330; incentive effects of competition; behavioral industrial organization